2019
DOI: 10.1007/s40265-019-01086-0
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Pharmacological and Pharmacokinetic Profile of Teneligliptin: Implications for Clinical Practice

Abstract: Teneligliptin is a dipeptidyl peptidase-4 (DPP-4) inhibitor that was approved for the treatment of type 2 diabetes mellitus (T2DM) in Japan and Korea and is being researched in several countries. Teneligliptin is a potent, selective, and long-lasting DPP-4 inhibitor with a t ½ of approximately 24 h and unique pharmacokinetic properties: it is metabolized by cytochrome P450 (CYP) 3A4 and flavin-containing monooxygenase 3 (FMO3), or excreted from the kidney in an unchanged for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 79 publications
0
44
0
Order By: Relevance
“…This surveillance revealed that the incidence of any ADRs in teneligliptin-treated patients was 3.85% and serious ADRs in 1.09%. Of note, the overall rate of ADRs did not exceed the rates observed in clinical trials (9.48% of 1645 patients) [23] or over 1 year in clinical trials (6.7-18.9%) [13] in Japan. The safety profile of teneligliptin in this surveillance was generally similar to those reported for other DPP4 inhibitors [30][31][32][33][34][35][36].…”
Section: Safety In Overall Populationmentioning
confidence: 92%
See 2 more Smart Citations
“…This surveillance revealed that the incidence of any ADRs in teneligliptin-treated patients was 3.85% and serious ADRs in 1.09%. Of note, the overall rate of ADRs did not exceed the rates observed in clinical trials (9.48% of 1645 patients) [23] or over 1 year in clinical trials (6.7-18.9%) [13] in Japan. The safety profile of teneligliptin in this surveillance was generally similar to those reported for other DPP4 inhibitors [30][31][32][33][34][35][36].…”
Section: Safety In Overall Populationmentioning
confidence: 92%
“…Teneligliptin, a DPP4 inhibitor, was approved in Japan in 2012 and subsequently in Korea in 2014 [13]. The clinical trials for teneligliptin demonstrated its efficacy and safety as monotherapy [14,15] or in combination with oral antidiabetic agents or insulin [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dapagliflozin, canagliflozin, and empagliflozin also have approved FDCs with metformin [16]. In addition, dapagliflozin and empagliflozin are widely available as FDCs with saxagliptin and linagliptin, respectively [16]; a canagliflozin/ teneligliptin FDC has recently been approved in Japan [17]. This review will focus primarily on the phase I pharmacokinetics (PK) and pharmacodynamics (PD) of the ertugliflozin stand-alone therapy.…”
Section: Key Pointsmentioning
confidence: 99%
“…Teneligliptin, a DPP4 inhibitor, is currently approved in Japan and Korea for the treatment of T2DM [ 9 – 11 ]. In Japan, it is prescribed at a starting dose of 20 mg once daily, but its dose can be increased to 40 mg once daily if the glucose-lowering effect of 20 mg once daily is insufficient.…”
Section: Introductionmentioning
confidence: 99%